Effects of a 12-week change-of-direction sprints training program on selected physical and physiological parameters in professional basketball male players - Brini, Seifeddine (2020)
Multidirectional repeated sprints with quick changes-of-direction (CoD) are considered a key performance determinant in basketball. The objective of this study was to investigate the effects of a 12-week CoD sprint training program compared to regular basketball training on selected measures of physical fitness and physiological adaptations in male basketball players. Sixteen professional basketball players were randomly assigned to an intervention group (INT = 8) or an active control group (CON = 8). INT completed a 12-week CoD sprint training program with two sessions per week while CON continued their regular training. Training volume was similar between groups. Before and after the intervention, the two groups were evaluated for the repeated sprint ability test with CoD (IRSA5COD), the squat jump (SJ) and countermovement jump (CMJ) test, the five time-jump test (FJT) and change of direction T-test. Blood samples were taken before the beginning of the experimental protocol, after 4, 8 and 12 weeks to monitor the testosterone/cortisol ratio (T/C). For T-test, post-hoc tests revealed significant pre-to-post improvements for INT (3.4%; p = 0.001, ES = 0.91). For CMJ, post-hoc tests revealed a significant pre-to-post decrease for INT (−11.6%; p = 0.001, ES = 0.94), and a significant improvement for CON (4.96%; p = 0.014, ES = 0.60). For T/C ratio, post-hoc tests revealed a significant decrease after 12 weeks of training for INT (52.3%; p < 0.001; ES = 0.63). In conclusion, twelve weeks of CoD sprint training enhanced CoD performance but negatively affected vertical jump capacity in male basketball players. T/C ratio indicated that the physiological demands associated with INT were well-balanced.